2018
DOI: 10.1590/1413-81232018234.09962016
|View full text |Cite
|
Sign up to set email alerts
|

Internação e mortalidade por quedas em idosos no Brasil: análise de tendência

Abstract: Fall-related mortality and admission rates increased in Brazil but varied by gender and state of residence. The results of this study do not only monitor the problem over time but may also help plan technological and human resources to prevent and control falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
81

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 17 publications
4
34
0
81
Order By: Relevance
“…This emphasizes that use of three or more drugs acting on the central nervous system should be avoided in the geriatric population. 29 Occurrences of drug interactions were positively associated with the number of drugs used, which was in line with other published studies. 30,31 A retrospective study in which the trends and determinants of polypharmacy among patients discharged from an internal medicine unit in a teaching hospital were measured showed that the risk factors for polypharmacy were age older than 75 years, high CCI and multiple morbidities.…”
Section: Discussionsupporting
confidence: 90%
“…This emphasizes that use of three or more drugs acting on the central nervous system should be avoided in the geriatric population. 29 Occurrences of drug interactions were positively associated with the number of drugs used, which was in line with other published studies. 30,31 A retrospective study in which the trends and determinants of polypharmacy among patients discharged from an internal medicine unit in a teaching hospital were measured showed that the risk factors for polypharmacy were age older than 75 years, high CCI and multiple morbidities.…”
Section: Discussionsupporting
confidence: 90%
“…No Brasil, a taxa de óbitos em idosos entre 1997 e 2010 superou 30/100.00 habitantes, e 0,61% dos óbitos foram ocasionados em decorrência de quedas 12 . A taxa de mortalidade de idosos em decorrência de quedas nas capitais brasileiras aumentou 200% entre 1996 e 2012, passando de 1,25 para 3,75/10.000 idosos com incremento de 15% ao ano 14 .…”
Section: Discussionunclassified
“…O Brasil, o Distrito Federal e mais 20 capitais federais apresentaram tendência de aumento nas taxas de mortalidade para o sexo masculino e feminino, segundo estudo de Abreu e colaboradores 14 . As quedas no sexo masculino estão associadas ao maior envolvimento do homem em atividades físicas intensas e perigosas, ignorando os limites de sua capacidade física [14][15][16] . Dentre as limitações deste estudo, destacamos a elevada proporção de óbitos cuja natureza da queda não tenha sido especificada (44,3%).…”
Section: Discussionunclassified
“…Concomitantemente a essas alterações na estrutura etária do país, devidas ao crescimento de longevos, o acúmulo de doenças relacionadas ao envelhecimento é mais evidenciado, intensificando a demanda por atendimento em serviços de saúde e elevando exponencialmente os gastos no Sistema Único de Saúde (SUS) com internações hospitalares e cuidados médicos (4,5) . Só no ano de 2013 há registros de 93.312 internações no SUS em decorrência de queda entre idosos acima de 60 anos, triplicando após os 65 anos, sem contar os gastos no tratamento de fraturas (6,7) .…”
Section: Introductionunclassified